SPEAKING DIFFICULTIES FACED BY SECOND GRADE STUDENTS AT ISLAMIC BOARDING SCHOOL IN TASIKMALAYA - Silvi Sultonah (Journal of Applied Linguistics (ALTICS), 2024)
Speaking is an important skill in English with aim to be able to communicate orally. Learners from English as Second Language (ESL) countries often faced difficulty in learning English especially in speaking with various factors. This study aimed to find the factors of eight-grade students’ difficulty in speaking from non- linguistic factor. The researcher used qualitative method with ethnography as research design to find out students’ speaking difficulties factors. This research has six respondents from eight-grade students at an Islamic boarding school in Tasikmalaya with purposive sampling. Research data were analyzed by using triangulation that included observation, interview, and questionnaire. The findings of this research are: (1) linguistic factors that found by researchers are lack of vocabulary, lack of pronunciation, and lack of grammar that impacted students’ speaking performance. (2) non-linguistic factors that found by researcher are psychological factors such as shyness, anxiety, and lack of confidence which affected students’ speaking performance. Keywords: Speaking difficulty, non-linguistic factors, psychological factors.